2020
DOI: 10.1101/2020.05.14.096677
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The effect of vascular health factors on white matter microstructure mediates age-related differences in executive function performance

Abstract: Even within healthy aging, vascular risk factors can detrimentally influence cognition, with executive functions (EF) particularly vulnerable. Fronto-parietal white matter (WM) connectivity in part, supports EF and may be particularly sensitive to vascular risk. Here, we utilized structural equation modeling in 184 healthy adults (aged 20-94 years of age) to test the hypotheses that: 1) fronto-parietal WM microstructure mediates age effects on EF; 2) higher blood pressure (BP) and white matter hyperintensity (… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 121 publications
(126 reference statements)
0
4
0
Order By: Relevance
“…In human studies, recent work suggests that executive function is associated with WM integrity, rather than volume. 95,96 In ongoing work, we are actively investigating WM integrity in association with cognitive function using DTI in these aging vervets.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In human studies, recent work suggests that executive function is associated with WM integrity, rather than volume. 95,96 In ongoing work, we are actively investigating WM integrity in association with cognitive function using DTI in these aging vervets.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, we reported declines in executive function with age in the 30 female vervets in the ongoing longitudinal study (Frye et al 38 ). In human studies, recent work suggests that executive function is associated with WM integrity, rather than volume 95,96 . In ongoing work, we are actively investigating WM integrity in association with cognitive function using DTI in these aging vervets.…”
Section: Discussionmentioning
confidence: 99%
“…Its function is not clear, but it has been suggested to play an important role in executive function 37 . The findings of a recent study showed that the IFOF and the fronto‐parietal white matter of the genu of the corpus collosum mediate the association between age and executive function in healthy aging and that the WMH burden within these white matter tracts influences this association 38 . This implies that the related fibers may play an important role as carriers underlying brain‐behavior associations.…”
Section: Discussionmentioning
confidence: 99%
“…Among the MDD participants, we expect switching performances to be associated with thinner cortices among cortical regions involved in executive functions such as the frontal gyri ( Yuan and Raz, 2014 ) and semantic VF (such as the temporal cortices) ( Vonk et al, 2019 ). Similarly, we expected decreased FA among white matter tracts both involved in cognitive switching, semantic classification and verbal fluency, such as the superior longitudinal fasciculus (SLF) and the inferior fronto-occipital fasciculus (IFOF) ( Hoagey et al, 2021 , Garcin et al, 2018 , Li et al, 2017 ).…”
Section: Introductionmentioning
confidence: 95%